Kevin’s Individuation Process in Split (2017) - Agista Girindrani Santoso (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
Analytical psychology by Jung discusses the psyche. The soul includes conscious and unconscious physical events. According to Jung, the collective unconscious and archetypes are two components of the unconscious, and it is from these two that individuation will take place. The Carl Jung theory is applied in this work. The persona, shadow, anima/animus, and self-archetypes. The four main categories in Jung's theory are covered in this study. The purpose of this study is to determine how the individuation process contributes to the development of the main character's personality in the movie. According to the findings of this study, Kevin's ability to go through the process of individuation and reconnect with his true self is what makes The Beast the most significant archetype in this movie.